Development and in Vitro Characterization of Niosomal Carriers Niosomal Carriers for Sustained Drug Delivery - Hosseinzadeh Gavon, Alireza; Khanpour, Mojtaba; Farrokh Pour, Milad (Biocompounds, 2025)
Drug delivery systems are designed to enhance bioavailability while overcoming the limitations of conventional dosing strategies. Vesicular carriers, such as niosomes, have attracted attention for their excellent stability, cost-effectiveness, and sustained-release properties. Niosomes can encapsulate both lipophilic and hydrophilic drugs, making them versatile carriers for a wide range of therapeutics. Recent studies have focused on optimizing niosomes for targeted drug delivery, exemplified by the encapsulation of 4-Hydroxyisoleucine (4-HIL) for diabetes management. In this study, 4-HIL isolated from fenugreek seeds was incorporated into niosomes and PEGylated niosomes using the thin-film hydration method. The resulting 4-HIL-loaded niosomes exhibited semi-spherical, smooth morphologies with a particle size of ~200 nm, a Zeta Potential (ZP) of -22 mV, and entrapment efficiencies ranging from 55.1% to 87.1%. Fourier-Transform Infrared (FTIR) spectroscopy confirmed hydrogen bonding between Span 60 and cholesterol within the niosomal structure. PEGylation increased vesicle sizes to 460–580 nm and improved entrapment efficiencies to 75.43–90.1%, highlighting the potential of this formulation as a promising carrier for antidiabetic therapy.